PEMBUATAN DAN KARAKTERISASI METIL SELULOSA DARI BONGGOL DAN KULIT NANAS (Ananas comosus) - Lena Rahmidar; Seruni Wahidiniawati; Tety Sudiarti (University of Bengkulu, 2018)
[MAKING AND CHARACTERIZATION OF CELLULOSE METHOD OF BONGGOL AND LEATHER LEATHER (Ananas comosus)] Wastes of core and peel of pineapple are often not utilized properly, in fact the waste has nutritional content that can be useful. Carbohydrate content in the waste is large enough and allows to be utilized. The purpose of this research is for converting glucose into cellulose and synthesized into methylcellulose. The first stage is glucose from core and peel of pineapple converted into microbial cellulose with Acetobacter xylinum bacteria with the addition of nitrogen and carbon sources. The second stage is synthesis of methylcellulose with methylene chloride and the solvent aquadest/acetone. The dried microbial cellulose was firstly swelled with NaOH addition, then methylation by addition of solvent and methylene chloride and then refluxed at 50-60. Then methyl cellulose neutralized, washed and dried at 50.The FTIR results showed typical cellulose uptake for cellulose microbial pineapple core at wave number 3377.36 cm-1 for OH bonds and 2935.66 cm-1 for CH bonds and in cellulose microbialpineapple peel at wave number 3377.36 cm-1 for OH bonds and 2935.66 cm-1 for the CH bonds. The ratio OH/CH of methyl cellulose-acetone has a smaller value in the core and peel of pineapple concluded that acetone is more efficient to use as a solvent at the methylation. The substitution value of the core and peel of pineapple skin is estimated to below based on the solubility test results.